Effect of synchrotron X‐ray radiation damage on phase transitions in coordination polymers at high pressure. Issue 2 (17th March 2022) - Collings, Ines E.; Hanfland, Michael
Abstract : The impact of X‐ray irradiation on the high‐pressure phase‐transition behaviour of coordination polymers is highlighted with four example studies. Abstract : The high‐pressure phase‐transition behaviour of metal–organic frameworks and coordination polymers upon varying degrees of X‐ray irradiation are highlighted with four example studies. These show that, in certain cases, the radiation damage, while not extreme in changing unit‐cell values, can impact the existence of a phase transition. In particular, pressure‐induced phase transitions are suppressed after a certain absorbed dose threshold is reached for the sample. This is thought to be due to partial amorphization and/or defect formation in the sample, hindering the co‐operative structural distortions needed for a phase transition. The high‐pressure experiments were conducted with several crystals within the sample chamber in order to measure crystals with minimal X‐ray irradiation at the highest pressures, which are compared with the crystals measured continuously upon pressure increase. Ways to minimize radiation damage are also discussed within the frame of high‐pressure experiments.